The philosophization of Ash'ari's teaching - Džilo Hasan; Mehmedi Šinazi (Kom: Časopis za Religijske Nauke, 2018)
The purpose of this paper is to show that the theological thought in Islam also contains philosophical findings of crucial importance in the history of ideas. Striking examples of such a philosophical discourse are al-Baqillani, al-Ghazali and Fakhruddin Razi. Taking Ash'ari's teachings as a starting point, they significantly deepened some of the philosophical views that were also discussed in European philosophy after the Renaissance. Al-Baqillani contended that dealing with metaphysics was necessary for the crystallization of religious teachings. He opted to reflect upon substance, accidents, existents, the rift among the existents, as well as on the multitude and other questions. Al-Ghazali broke the metaphysical monotony of the time by revealing not only truths but also misconceptions in metaphysical discussions, while providing supporting evidence and showing a strong dialectical and logical ability. Fakhruddin Razi went so far as to compare wisdom with Kalām, believing that Kalām is, in fact, the one true wisdom. His works show that he tackled every significant philosophical debate to date. The arguments of these religious philosophers are clear evidence of the theologization of philosophy or the philosophization of theology.